The Relationship of Covid-19 Risk Perception with Health Protocol Compliance in Universitas Negeri Makassar Students - Muhammad Rahmat; Muh. Daud; Muh. Nur Hidayat Nurdin (PT ARRUS Intelektual Indonesia, 2023)
The Covid-19 pandemic has entered its third year and still shows no signs of ending, this is due to the low compliance to health protocols which is influenced by individual assessments of the risk from Covid-19 itself. This study aims to determine the relationship between Covid-19 risk perception and health protocols compliance of Universitas Negeri Makassar students. This research uses quantitative methods. Respondents in this study were 211 students at Universitas Negeri Makassar. Hypothesis testing in this study using Product Moment. The results of the hypothesis test showed a correlation value of r = 0.563 with a significance value of p = 0.000 (p < 0.05). This means that there is a relationship between the Covid-19 risk perception and health protocols compliance of Universitas Negeri Makassar students. The correlation value shows a positive value which means that Covid-19 risk perception and health protocols compliance is positively correlated and is in the moderate category. The positive correlation value indicates that the higher the students Covid-19 risk perception, the higher the health protocols compliance. Conversaly, the lower the Covid-19 risk perception that students have, the lower the health protocols compliance. This research contributes to the fields of Social Psychology and Political Psychology related to student reactions and behavior in pandemic situations.